1998
DOI: 10.1016/s0895-7061(97)00459-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Costs of Antihypertensive Medications in a Developing Country A Study in Mexico Comparing 1990 and 1996

Abstract: In developing countries, the cost of antihypertensive medications is one of the principal limiting factors when trying to treat patients with high blood pressure. To determine the changes in cost (in US dollars) of these medications and in the percentage of the minimum wage needed to purchase them, two cost studies (1990 and 1996) done in Mexico were compared. The yearly cost of a treatment with hydrochlorothiazide was US $13.80 in 1990; in 1996 it was US $10.92. Both figures represent 1.1% of the minimum wage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Second, there is a gap relating to delivery setting: most studies concentrated on hospital care, with very few studies including economic aspects of CVD care in primary and community care. Only two studies estimated the costs of prevention, one in Mexico [32] and another in China [33]. Given the importance of prevention and service delivery at these levels, particularly as more innovative models are being rolled out at these levels in low-resource settings, there would be great value in exploring them as a matter of priority [9].…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is a gap relating to delivery setting: most studies concentrated on hospital care, with very few studies including economic aspects of CVD care in primary and community care. Only two studies estimated the costs of prevention, one in Mexico [32] and another in China [33]. Given the importance of prevention and service delivery at these levels, particularly as more innovative models are being rolled out at these levels in low-resource settings, there would be great value in exploring them as a matter of priority [9].…”
Section: Discussionmentioning
confidence: 99%
“…A Mexican study found that hydrochlorothiazide was the only treatment option that did not become less affordable between 1990 and 1996; 1.1% of the minimum wage was needed to pay for chronic treatment. Other CVD medicines increased up to threefold in price and treatment cost as much as 47% of the minimum wage [7]. A study performed in Ghana found that 93% of patients did not comply with their antihypertensive treatment regimen, 96% of which reported high medicine prices as the reason for not complying [8].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of hypertension and its cardiovascular sequel account for a significant proportion of the total expenditure for health care in many countries [1,2,[6][7][8]. Antihypertensive treatment should, in addition to lowering blood pressure, reduce the incidence of cardiovascular morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%